The Role of Feedback Frequency and Valence in Optimizing Motor Task Performance: Interaction with Physiological Arousal. - Kumar Saxena, Mitali Praveen; Reddy Ganuthula, Venkat Ram (Journal of Sport Behavior, 2025)
Feedback is an essential stimulus influencing an individual's emotional state and performance. However, there is a lack of agreement among experts regarding the ideal frequency of feedback to achieve optimal results in motor tasks. This study examined how feedback frequency and valence affect individuals' motor skill acquisition, performance, and emotional responses. We also propose the optimal feedback frequency and valence condition to maximize performance. Further, we hypothesized that arousal level would impact the relationship between feedback and performance in motor tasks. Since adolescence is a critical stage for acquiring motor skills. 120 schoolchildren were tested with different feedback frequencies and valences. The experiment measured task performance in a dart-throwing game and emotional reactions to feedback manipulation. Electrodermal activity measured the emotional responses using physiological arousal as a metric. The findings suggest that both the frequency and positivity of feedback had a substantial impact on the average task performance of the students. The highest level of performance was observed when positive feedback was given frequently. There was no notable disparity in the average arousal levels across the different feedback situations. The study also revealed no effect of feedback frequency on motor skill learning. However, frequent feedback improved learning results over self-evaluation. In addition, arousal levels moderated the relationship between feedback and task performance. These findings establish a foundation for providing the most effective feedback frequency to improve the acquisition of motor skills and performance outcomes while also considering the emotional response of the recipients.